Responsabilidad del propietario y/o arrendador de locales comerciales por contribuir o facilitar infracciones y delitos contra la propiedad industrial - Barrera Taboada, Adriana (2021)
Counterfeiting and piracy are serious problems in today’s society. Normally, direct actors and infringers are held responsible for violations of industrial property rights and copyrights, but there are third parties or indirect actors who can be held responsible for these illegal behaviors that affect the normal development of trade in the market.